PROBLEM SOLVING MAHASISWA PROGRAM STUDI AGRIBISNIS PADA MASA COVID-19 DI UNIVERSITAS TRIBHUWANA TUNGGADEWI - yanti; Wahidyanti Rahayu Hastutiningtyas (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2022)
Introduction: Education is one of the factors affected by the Covid-19 disease. school activities or any group activities are being transferred to online or online this is due to prevent the spread and development of the covid-19 virus. Undergraduate students (S1) during the COVID-19 period are required to think more critically and be able to provide innovations in dealing with the Covid-19 period. Problem solving is the key for students in overcoming the problems they are currently facing. Methods: Analytical observation is the design of this study, where the population is 63 respondents, while the research sample is 50 respondents using simple random sampling. The research was conducted on 7th semester students of the Agribusiness study program at Tribhuwana Tunggadewi University. The data were taken using The Attitudes Toward Problem Solving Scale (ATPSS) questionnaire and validity test was carried out using Pearson Product Moment (r) and reliability test with a value of 0.998 so that it was declared reliable. Results: analyzed univariately and presented in a frequency distribution. The result is that students of the agribusiness study program have sufficient problem solving. The accuracy of problem solving can make it easier to solve problems for students of the agribusiness study program at Tribhuwana Tunggadewi University.